Vocational training of nurses in the study bridging-conscious choice or necessity? - Stanisławska, Marzanna; Cybulska, Teresa; Jurczak, Anna; Wieder-Huszla, Sylwia; Smalec, Maria; Pilch, Dorota; Augustyniuk, Katarzyna; Grochans, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The ’90s of the twentieth century was the beginning of a transformation in the education system of Polish nurses. In accordance with the Directive 2005/36/WE of the European Parliament and the Council, nurses could finally obtain professional qualifications at the level obligatory in the European Union. Aim. The purpose of this study is to analyze opinions of nurses on bridging courses. Material and methods. The study involved 320 nurses, including 315 women and 5 men. The respondents were professionally active nurses from the region of West Pomerania. They were divided into two groups: the study group (207) – nurses who were studying or had completed bridging studies, and the control group (113) – nurses who had not decided to raise their education levels. The research tools were two original questionnaires. Results. For most respondents bridging studies (77.5%) are a consequence of a consciously taken decision. For many of them, however studies are a necessity. Conclusions. 1. Bridging studies are an opportunity to obtain a professional nurse degree in accordance with the EU requirements. They increase motivation to improve professional skills and give a sense of professional stability. 2. According to non-participants of bridging courses, studies are for most nurses a necessity resulting from the unfavorable record of the Accession Treaty. Studies give the possibility of working as a nurse in another country, motivate to improve professional skills, and strengthen professional prestige. Many respondents perceive bridging studies as a waste of time and money.